Oral Administration of a Seed-based Bivalent Rotavirus Vaccine Containing VP6 and NSP4 Induces Specific Immune Responses in Mice - Feng, Hao; Li, Xin; Song, Weibin; Duan, Mei; Chen, Hong; Wang, Tao; Dong, Jiangli (Frontiers in Plant Science, 2017)
Rotavirus is the leading cause of severe diarrheal disease among newborns. Plant-based rotavirus vaccines have been developed in recent years and have been proven to be effective in animal models. In the present study, we report a bivalent vaccine candidate expressing rotavirus subunits VP6 and NSP4 fused with the adjuvant subunit B of E. coli heat-labile enterotoxin (LTB) in maize seeds. The RT-PCR and Western blot results showed that VP6 and LTB-NSP4 antigens were expressed and accumulated in maize seeds. The expression levels were as high as 0.35 and 0.20% of the total soluble protein for VP6 and LTB-NSP4, respectively. Oral administration of transgenic maize seeds successfully stimulated systemic and mucosal responses, with high titers of serum IgG and mucosal IgA antibodies, even after long-term storage. This study is the first to use maize seeds as efficient generators for the development of a bivalent vaccine against rotavirus.